Implementasi Program Kecamatan Tangguh Bencana (KENCANA) sebagai Upaya Mitigasi Bencana di Kecamatan Padang Utara - Shizuka Nelsi, Yurike; Alhadi, Zikri (Policy, Law and Political Research Center, 2024)
This research aims to describe the implementation of the Disaster Resilient Sub-district (KENCANA) program as a disaster mitigation effort in the North Padang Sub-district and identify the inhibiting factors. This research uses a qualitative approach with descriptive methods. Research informants were selected using a purposive sampling technique, while data were collected through interviews, observation and documentation. Data validity was tested using triangulation techniques, and data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that implementing the KENCANA program in North Padang Sub-district, based on Merilee S. Grindle's implementation model, has yet to run optimally. Several aspects, such as implementing activities, program funding, community interest, and supporting facilities and infrastructure, have yet to be well implemented. The main obstacles include low community awareness and concern, limited budget and infrastructure, and lack of adequate socialization and training.